Incidence of sulphasalazine-induced male infertility. Issue 6 (June 1981) - Birnie, G G; McLeod, T I; Watkinson, G
Abstract : Sperm analysis of 21 patients taking sulphasalazine for inflammatory bowel disease revealed that 86% had abnormal semen analysis and 72% had oligospermia.